The Nexus of Directed Motivational Current (DMC) and Learning Autonomy in English for Specific Purposes (ESP): A Reframing of Student Self-Regulating and Motivation - Aswin Abbas; Syarifuddin Dollah; Andi Anto Patak (Institut Agama Islam Negeri Palopo, 2024)
This study examines the nexus between Directed Motivational Current (DMC), a novel motivational theory, applied linguistics, and student learning autonomy within English for Specific Purposes (ESP) contexts. The objectives are to understand how students describe and experience a DMC and how the DMC reframes students’ perceptions of their learning autonomy and self-regulation. Using a qualitative case study with 13 participants from a private vocational campus in Ternate, North Maluku, Indonesia, who were systematically selected, the research identified two main themes: DMC as an unstoppable flow state and reframing autonomy from the right to vote to Self-Governance. Additionally, the study revealed a significant and transformative connection between DMC and student autonomy in ESP learning. DMC acts as a catalyst that reshapes students' understanding of autonomy, going beyond mere self-governance, driven by self-directed learning (SRL). The findings suggest that clear, intense objectives in DMC support and sustain proactive SRL behaviours, such as self-supervision and environmental management, which are crucial for achieving specific and challenging ESP objectives. These findings have implications for ESP teaching and curriculum design. Instructors should encourage students to make informed choices and help them set goals to trigger DMCs, such as through authentic projects linked to their careers. Instruction should focus on teaching self-regulation strategies to sustain DMC flow, rather than adding extra tasks. ESP educators should empower students to create their own disciplined learning rules, rather than just passively following the curriculum.